Engineering biomaterials to 3D-print scaffolds for bone regeneration: practical and theoretical consideration. (5th May 2022) - Ansari, Mohammad Aftab Alam; Golebiowska, Aleksandra A.; Dash, Madhusmita; Kumar, Prasoon; Jain, Prashant Kumar; Nukavarapu, Syam P.; Ramakrishna, Seeram; Nanda, Himansu Sekhar
Abstract : Composite 3D-printed mechanically competent scaffolds for bone tissue regeneration. Abstract : There are more than 2 million bone grafting procedures performed annually in the US alone. Despite significant efforts, the repair of large segmental bone defects is a substantial clinical challenge which requires bone substitute materials or a bone graft. The available biomaterials lack the adequate mechanical strength to withstand the static and dynamic loads while maintaining sufficient porosity to facilitate cell in-growth and vascularization during bone tissue regeneration. A wide range of advanced biomaterials are being currently designed to mimic the physical as well as the chemical composition of a bone by forming polymer blends, polymer–ceramic and polymer–degradable metal composites. Transforming these novel biomaterials into porous and load-bearing structures via three-dimensional printing (3DP) has emerged as a popular manufacturing technique to develop engineered bone grafts. 3DP has been adopted as a versatile tool to design and develop bone grafts that satisfy porosity and mechanical requirements while having the ability to form grafts of varied shapes and sizes to meet the physiological requirements. In addition to providing surfaces for cell attachment and eventual bone formation, these bone grafts also have to provide physical support during the repair process. Hence, the mechanical competence of the 3D-printed scaffold plays a key role in the success of the implant. In this review, we present various recent strategies that have been utilized to design and develop robust biomaterials that can be deployed for 3D-printing bone substitutes. The article also reviews some of the practical, theoretical and biological considerations adopted in the 3D-structure design and development for bone tissue engineering.